2017
DOI: 10.1080/15402002.2017.1312404
|View full text |Cite
|
Sign up to set email alerts
|

Poor Sleep Is Associated With Greater Marital Aggression: The Role of Self Control

Abstract: Sleep problems were associated with higher levels of aggression on all measures, and lower self-control mediated these associations. Associations did not depend on participant gender, presence of children in the home, income, or length of marriage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 27 publications
(29 reference statements)
0
20
1
Order By: Relevance
“…Further, these relationships were examined in married couples in a manner that accounted for shared variance among partners. This is an especially important addition to the literature on couples and sleep as previous research examining sleep in couples has done so without accounting for the nonindependent nature of dyadic data (Keller, Haak, DeWall, & Renzetti, 2017; Segrin & Burke, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Further, these relationships were examined in married couples in a manner that accounted for shared variance among partners. This is an especially important addition to the literature on couples and sleep as previous research examining sleep in couples has done so without accounting for the nonindependent nature of dyadic data (Keller, Haak, DeWall, & Renzetti, 2017; Segrin & Burke, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, couples reporting poor sleep showed greater in ammatory responses as measured by interleukin-6 during a con ict compared to couples who reported a better sleep (Wilson et al, 2017). Self-reported sleep problems have also been shown to correlate with more marital aggression (Keller, Haak, DeWall, & Renzetti, 2019). Interestingly, the relationship between sleep problems and marital aggression was mediated by lower levels of self-control (Keller et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Self-reported sleep problems have also been shown to correlate with more marital aggression (Keller, Haak, DeWall, & Renzetti, 2019). Interestingly, the relationship between sleep problems and marital aggression was mediated by lower levels of self-control (Keller et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It should also be noted that another key factor which contributes to developing healthy habits is sleep. This is essential in childhood, as it contributes to cognitive development (Keller, Haak, DeWall, and Renzetti, 2019). Similarly, it has been shown that during sleep neuronal waste that accumulates during wakefulness is eliminated, which facilitates proper cognitive functioning, increased emotional state and strengthening of the immune system (Mireku et al, 2019).…”
Section: Introductionmentioning
confidence: 99%